Neue Orientierungen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Aktuelle Aspekte in der Ernährungsbildung und -beratung. Tagungsband der DGE-Arbeitstagung am 29. und 30. September in Paderborn)

Ernährungs- und Verbraucherbildung in der Reform - Schlegel-Matthies, Kirsten (Pisa“ in der Verbraucherbildung. Sind wir alle Konsum-Analphabeten?)

Fachdidaktische Perspektiven auf den Umgang mit Heterogenität im haushaltsbezogenen Unterricht - Schlegel-Matthies, Kirsten (Heterogenität als Chance. Vom produktiven Umgang mit Gleichheit und Differenz in der Schule.)

Zwischen Selbstbestimmung und Verantwortung – Herausforderungen für Verbraucherbildung - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Verbraucherbildung vor neuen Herausforderungen. Editorial - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Finanzwirtschaft Finanzdienstleistungen Empirische Wirtschaftsforschung

Transparent Data Structures, or How to Make Search Trees Robust in a Distributed Environment - Korzeniowski, Miroslaw; Scheideler, Christian (ISPAN)

Supervised Peer-to-Peer Systems - Kothapalli, Kishore; Scheideler, Christian (ISPAN)

Efficient Broadcasting and Gathering in Wireless Ad-Hoc Networks - Onus, Melih; W. Richa, Andrea; Kothapalli, Kishore; Scheideler, Christian (ISPAN)

Constant density spanners for wireless ad-hoc networks - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; W. Richa, Andrea (SPAA)

How to spread adversarial nodes?: rotate! - Scheideler, Christian (STOC)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Verfahren und Vorrichtung zur Direktverschraubung - Meschut, Gerson; Küting, Jens

Fügeverfahren zum Verbinden von überlappend angeordneten Fügeteilen und entsprechende Fügevorrichtung - Freitag, Volker; Hahn, Ortwin; Meschut, Gerson; Ruther, Michael; Timmermann, Rüdiger; Wiese, Thomas

Design, analysis, and evaluation of a data structure for distributed virtual environments - Fischer, Matthias

Virtual and augmented reality support for discrete manufacturing system simulation - Dangelmaier, Wilhelm; Fischer, Matthias; Gausemeier, Jürgen; Grafe, Michael; Matysczok, Carsten; Mueck, Bengt (Computers in Industry)
Nowadays companies operate in a difficult environment: the dynamics of innovations increase and product life cycles become shorter. Furthermore products and the corresponding manufacturing processes get more and more complex. Therefore, companies need new methods for the planning of manufacturing systems. One promising approach in this context is digital factory/virtual productionthe modeling and analysis of computer models of the planned factory with the objective to reduce time and costs. For the modeling and analysis various simulation methods and programs have been developed. They are a highly valuable support for planning and visualizing the manufacturing system. But there is one major disadvantage: only experienced and long trained experts are able to operate with these programs. The graphical user interface is very complex and not intuitive to use. This results in an extensive and error-prone modeling of complex simulation models and a time-consuming interpretation of the simulation results. To overcome these weak points, intuitive and understandable manmachine interfaces like augmented and virtual reality can be used. This paper describes the architecture of a system which uses the technologies of augmented and virtual reality to support the planning process of complex manufacturing systems. The proposed system assists the user in modeling, the validation of the simulation model, and the subsequent optimization of the production system. A general application of the VR- and AR-technologies and of the simulation is realized by the development of appropriate linking and integration mechanisms. For the visualization of the arising 3D-data within the VR- and AR-environments, a dedicated 3D-rendering library is used.

Multi-User Support and Motion Planning of Humans and Humans Driven Vehicles in Interactive 3D Material Flow Simulations - Fischer, Matthias; Mueck, B.; Mahajan, K.; Kortenjan, M.; Laroque, C.; Dangelmaier, W. (Proceedings of the Winter Simulation Conference)

Waveguide-plasmon polaritons in photonic crystal slabs with metal nanowires - Tikhodeev, S. G.; Gippius, N. A.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Giessen, H. (physica status solidi (c))

Learner English: Ein Überblick über vorhandene Korpora und mögliche Forschungsansätze - Mindt, Ilka (Korpuslinguistik Deutsch: synchron – diachron – kontrastiv. Würzburger Kolloquium 2003)

Corpora in Applied Linguistics - Mindt, Ilka; Hunston, Susan (ICAME Journal 29, Computers in English Linguistics)